THE EFFECT OF TEACHING STRATEGIES AND SELF REGULATION ON STUDENTS’READING COMPREHENSION - Irmayanti Irmayanti; Didik Santoso; Rahmad Husein (Universitas Negeri Medan, 2018)
The objectives of this experimental research were to find out whether: (1)The students’ achievement in reading comprehension taught by using Read, Ask, Put, and Paraphrasing (RAPP) strategy was higher than that taught by using Direct, Reading Thinking, Active (DRTA) strategy, (2) the students’ achievement in reading comprehension with high self-regulation was higher than that low self-regulation, and (3) there was an interaction between teaching strategies and self-regulation on the students’ achievement in reading comprehension. The population of this research was the students in grade XII of Madrasah Aliyah Negeri Sipirok of 2016/2017 academic year. There were 63 students as samples of this research by applying cluster random sampling technique. The instruments of this research were reading comprehension test and questionnaire sheet. The data were analyzed using ANOVA at the level of significant α = 0.05. The result of the data analysis proved that: (1) the students’ achievement in reading comprehension taught by using RAPP strategy was higher than the students were taught by using DRTA strategy (2) the students’ achievement in reading comprehension with high self-regulation was higher than the students were given low self-regulation, (3) there was interaction between teaching strategies and self-regulation. The students’ achievement in reading comprehension is influenced by teaching strategies and self-regulation. Keywords: teaching strategies, self-regulation, reading comprehension